2022
DOI: 10.1039/d1na00892g
|View full text |Cite
|
Sign up to set email alerts
|

Foldable batteries: from materials to devices

Abstract: In this review, we summarize the recent progress in developing materials and system designs for foldable batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 200 publications
0
3
0
Order By: Relevance
“…Consequently, the 3D-printed Znion hybrid supercapacitor exhibited an areal energy density of 1.514 mWh•cm -2 with prolonged cyclability (capacitance retention of 100% over 10,000 cycles). Similarly, another study reported 3Dprinted Na-ion hybrid capacitors consisting of a nitrogen-doped Ti 3 C 2 T x (N-Ti 3 C 2 T x ) anode and AC positive electrode [23]. The porous N-Ti 3 C 2 T x enabled fast electron/ion pathways and electrochemical reaction kinetics, resulting in superior Na-ion storage behavior.…”
Section: Additive Manufacturingmentioning
confidence: 95%
“…Consequently, the 3D-printed Znion hybrid supercapacitor exhibited an areal energy density of 1.514 mWh•cm -2 with prolonged cyclability (capacitance retention of 100% over 10,000 cycles). Similarly, another study reported 3Dprinted Na-ion hybrid capacitors consisting of a nitrogen-doped Ti 3 C 2 T x (N-Ti 3 C 2 T x ) anode and AC positive electrode [23]. The porous N-Ti 3 C 2 T x enabled fast electron/ion pathways and electrochemical reaction kinetics, resulting in superior Na-ion storage behavior.…”
Section: Additive Manufacturingmentioning
confidence: 95%
“…Recently, design strategies inspired by paper artwork, named kirigami and origami, have been extensively applied to a wide range of electronics, encompassing antennas [ 78 ], image sensors [ 79 , 80 ], battery [ 81 , 82 ], and bioelectronics [ 83 , 84 ]. A kirigami-based structure involves cutting the edges or central parts of devices [ 85 , 86 ], while an origami-based structure involves the controlled folding of devices into desired patterns [ 87 , 88 , 89 ].…”
Section: Structural Approaches For the Fabrication Of Stretchable Ledsmentioning
confidence: 99%
“…In recent years, the demand for flexible lithium-ion batteries (FLIBs) has grown with the increasing popularity of flexible devices such as foldable smartphones and wearable accessories (Lee et al, 2013;Chen et al, 2021;Jeong et al, 2022). This trend is primarily driven by the development of foldable or flexible technologies, including cell phones, watches, and Internet of Things (IoT)-enabled electronics (Mokhtari et al, 2020;Woo et al, 2020;Lee et al, 2022).…”
Section: Introductionmentioning
confidence: 99%